Do certified cancer centers provide more cost‐effective care? A health economic analysis of colon cancer care in Germany using administrative data. Issue 10 (27th July 2021) - Cheng, Chih‐Yuan; Datzmann, Thomas; Hernandez, Diego; Schmitt, Jochen; Schlander, Michael
Abstract: Hospital certification has become an important measure to improve cancer care quality, with the potential effect of prolonging patient survival and reducing medical spending. However, yet to be explored is the cost‐effectiveness of cancer care provided in certified hospitals, considering significant additional costs incurred from certification requirements. We performed a cost‐effectiveness analysis (CEA) using two colon cancer populations (N = 1909) treated in different levels of certified hospitals (CHs) vs noncertified hospitals (NCHs) from a healthcare system's perspective. We matched patient‐level data of incident colon cancer cases, diagnosed between 2008 and 2013 from a large statutory health insurance in Saxony, Germany, to calculate net treatment costs by phase (initial, continuing and terminal phase). The costs were supplemented with extra costs from 31 additional services required for certification. Effectiveness measure was total survival time in life‐years. Outcome of interest was incremental costs per additional life‐year. The annualized net colon cancer treatment costs by phase showed a U shape with high costs in the initial (mean €26 855; 95% CI €25 058‐€28 652) and the terminal phases (mean €30 096; 95% CI €26 199‐€33 993). The base‐case CEA results and all sensitivity analyses consistently demonstrated longer survival and lower costs for the colon cancer cohort treated in CHs vs NCHs. To conclude, we used administrative data to derive the first cost‐effectiveness evidence supporting that colon cancer care delivered in the certified cancer centers in Germany improves survival outcomes and saves costs from a healthcare system's perspective. Generalization of the study results should be exercised with caution.